Mathematical Modelling of Induction Motor Transient Processes During Stator Winding Interruption - Konuhova, Marina; Orlovskis, Guntis; Ketners, Karlis (Electrical, Control and Communication Engineering, 2010)
This research presents induction motor mathematical model in coordinate axis's α, β, which allows to learn transient processes in rotor and stator circuits in the conditions of stator windings opening. Such kind of researches is nowadays actual due to impossibility of main calculated values measuring directly, but only on the stator terminals. Induction motor mathematical model forms Park-Gorev equations in α, β coordinate axis. It is preferable to use this coordinate system because it allows comparing the results of mathematical modeling in one of the phases with experimental data without transformations.